THE EMERGENCE OF MATERIALISM AND ISLAMIC VIEW UPON IT - Muttaqin Muttaqin (IAIN Surakarta, 2016)
Materialism is an understanding that states that something invisible (can’t be sensed) did not exist. That is, the unseen world (including God, angels, jinn, etc.) does not exist. Because it can’t be sensed by humans. So if so, how Islam views the concept? Where in the Islamic religion teaches the unseen world which is summarized in the pillars of faith. Automatic if Muslims agree with the materialism, then it will greatly affect the faith. For this reason, this paper tries to explain the essence of the concept of Materialism, by reviewing the definition and history, which at this time will review the opinions of the philosophers of ancient Greece is also one of the teachings of India, Carvaka. At the end of the analysis will be presented how should a Muslim respond to the concept of this materialism.